Bovine Immunogenetic Response to S. aureus and E. coli Mastitis: A Review - Bayan, Jyotishree; Sulabh, Sourabh (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The difference in the pattern of immune response between Escherichia coli and Staphylococcus aureus leads to different form of mastitis that they cause. A more hyper immune response by E. coli results in clinical mastitis whereas a subdued response of S. aureus changes the outcome to subclinical mastitis. The immune system of the animal recognises various antigens present in these bacteria (such as lipopolysaccharide, peptidoglycan and lipoteichoic acid) which induce or suppress the activity of major immune related genes resulting into the type of outcome the animal shows which either help the animal to recover quickly or may even amplify the response in such a way that causes discomfort or may even lead to death of the animal. This review reflects the importance and role of immune related genes involved in the mechanism of protection of the animal against two of the most common infectious bacterial agents, i.e., E. coli and S. aureus responsible for inducing inflammatory response in the mammary gland.